PENDAMPINGAN AKUNTANSI ZAKAT HARTA (AL-MAAL) - Susi Riani; Mugni Muhit (Jurnal Istimā, 2025)
The mentoring program on Zakat Wealth Accounting (al-maal) was conducted in response to the low level of public understanding regarding the calculation, recording, and distribution of zakat in accordance with Islamic jurisprudence and accounting standards, despite the high potential of zakat collection in Indonesia. This program aimed to improve zakat literacy by introducing the concepts of nisab, haul, zakat rates, and the practical calculation of various types of zakat able assets, including gold, silver, cash, business assets, agriculture, and livestock. The method employed involved socialization, calculation simulations, and hands-on practice in preparing zakat financial reports. The results indicate a significant increase in participants' skills in determining zakat obligations accurately, applying simple accounting records, and distributing zakat in a more accountable and measurable manner. This activity demonstrates that strengthening Zakat accounting capacity positively contributes to Zakat awareness and supports the optimization of zakat funds as an instrument of socio-economic empowerment. Therefore, this mentoring program is recommended to be continued in a sustainable manner and further developed through digital-based learning models to expand its impact and benefits.